Economic barriers to diagnostic equity: A multi-country analysis of patient costs for rapid SARS-CoV-2 testing in sub-Saharan Africa - Obinna Ekwunife; Collin Mangenah; Lucky Ngwira; Elizabeth Corbett; Karin Hatzold; Elvis Isere; John Bimba; Euphemia Sibanda; Frances M. Cowan; Godpower Omoregie; Gabrielle Bonnet (PLoS ONE, 2026)
While the acute phase of the COVID-19 pandemic has passed, understanding the economic barriers to diagnostic access remains critical for future pandemic preparedness and universal health coverage. Implementing efficient testing modalities is crucial to achieving optimal value for both clients and healthcare providers. This study examines the cost and affordability of various SARS-CoV-2 antigen rapid-diagnostic-test modalities in Nigeria, Malawi, and Zimbabwe from a client perspective, providing a blueprint for future diagnostic strategies in Sub-Saharan Africa. Testing was offered for free through professional testing and self-testing in government or NGO-led primary healthcare centers across all countries, and in community pharmacies and drug stores in Nigeria. Data were collected from October 2022 to May 2023 through a survey of a random sample of adults visiting participating sites. The survey collected patient costs, including transportation, medical and non-medical expenses, and productivity loss. Affordability was assessed by the incidence of catastrophic health expenditure (defined as costs exceeding 10% of household income). The unit patient cost of testing in Nigeria, Malawi and Zimbabwe was $4.2, $2.7 and $2.7, respectively. In Nigeria, testing in community pharmacies and drug stores was cheaper than in primary healthcare centers. Self-testing cost less than professional testing in Nigeria ($1.3 versus $9.8), but more in Zimbabwe ($3.2 versus $2.3). In Malawi, Nigeria and Zimbabwe 40.6%, 28.6%, and 5.7% of clients, respectively, faced catastrophic health expenditures. SARS-CoV-2 antigen testing imposes a significant financial burden on clients. Even “free” testing carries high indirect costs that threaten diagnostic equity. Diversified testing modalities, such as community pharmacies and drug stores, may offer lower-cost options for sustainable diagnostic integration.